2002
DOI: 10.1080/140174302753675339
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Structural Heart Disease Diagnosed In Utero

Abstract: Our data indicate that despite elective, planned delivery the prognosis for fetuses with in utero diagnosed heart defect was poor. The outcome was largely attributable to associated extracardiac malformations and chromosomal abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
46
2
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 17 publications
8
46
2
3
Order By: Relevance
“…These malformations had a more severe prognosis than existing cardiac pathology and therefore were the basic indication for TOP. There was a chromosomal anomaly incidence of 21.7% in our series, which is comparable to former studies (19)(20)(21). Additional systemic malformations are persuasive criteria for parents in making decisions regarding termination.…”
Section: Discussionsupporting
confidence: 77%
“…These malformations had a more severe prognosis than existing cardiac pathology and therefore were the basic indication for TOP. There was a chromosomal anomaly incidence of 21.7% in our series, which is comparable to former studies (19)(20)(21). Additional systemic malformations are persuasive criteria for parents in making decisions regarding termination.…”
Section: Discussionsupporting
confidence: 77%
“…La incidencia de alteraciones cromosómicas en los casos fallecidos del grupo B fue del 29%; en otras series, osciló entre el 28% y el 66%. [3][4][5][6][12][13][14][15] Coincidimos con la mayoría de los grupos en que las anomalías asociadas a CC con mayor frecuencia son las del SNC; en nuestra serie, fue más frecuente la agenesia del cuerpo calloso, pero en otros estudios la anencefalia, la hidrocefalia …”
Section: Discussionunclassified
“…Fasnacht MS [2] reported that the most common genetic disorders of these fetuses were: trisomy 13, 21 and 18, and micro deletion 22q11 Sy. Boldt T. [3] reported in his study that artificial abortion had an incidence of 35% and that 8% died in uterus. The frequency of genetic disorders was 28%.…”
Section: Discussionmentioning
confidence: 99%